Recreational activities and teaching ball handling in footballers from 8 to 10 years old (RIAF. International Journal of Physical Activity, 2023)
The teaching of ball control techniques in soccer has a significant impact on the sports field, providing practitioners with the necessary stimulus to learn technical gestures and motivating female players to prepare to reach the elite level and participate internationally in major global leagues. This study aims to determine the impact of recreational activities on the teaching process of ball control among young female soccer players aged 8 to 10. Consequently, theoretical resources from various authors were explored and analyzed in relation to the study's variables to design an instrument that addresses the identified problem.The methodology employed a mixed qualitative-quantitative approach, based on descriptive research. Scientific observation was used as a technique with a sample of 30 female soccer players aged 8 to 10, alongside interviews conducted with two soccer specialists as data collection methods. The results revealed a deficient ball control, highlighting challenges such as poor coordination and a low level of control over the ball.The study concludes by emphasizing the importance of implementing effective tools for teaching technical skills to children, aimed at developing abilities and proficiencies. Based on this, the use of a recreational activities guide is recommended during training sessions as a structured proposal for learning ball control, organized into the phases of initiation, organization, development, and conclusion.
Keywords: Recreational activities; Ball dominance; Teaching; Women's Football; Training